Prognostic value of TMEM59L and its genomic and immunological characteristics in cancer - Shi, Chang; Zhang, Lizhi; Chen, Dan; Wei, Hong; Qi, Wenjing; Zhang, Pengxin; Guo, Huiqi; Sun, Lei (Frontiers in Immunology, 2022)
Abstract Background: TMEM59L is a newly discovered transmembrane protein; its functions in cancer remain unknown. This study was designed to reveal the prognostic value and the functional role of TMEM59L in cancer. Methods: The gene expression profiles, methylation data, and corresponding clinical data of TMEM59L were retrieved from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression database. Survival analysis was employed to calculate the pan-cancer prognostic value of TMEM59L. The correlation between TMEM59L expression and tumor immune microenvironment, as well as DNA methylation dynamics and genomic heterogeneity across cancers were assessed based on data from TCGA. Results: Our findings revealed that distinct differences of TMEM59L mRNA expression were observed in different cancer types and that higher TMEM59L expression was observed in the advanced pathological stage and associated with worse prognosis in kidney renal papillary cell carcinoma, bladder urothelial carcinoma, colon adenocarcinoma, and kidney renal clear cell carcinoma. Pathway analysis indicated that TMEM59L exerted a key influence in cancer development and in immune- and cancer-associated pathways such as epithelial–mesenchymal transition and TGF-β signaling. Moreover, correlation analysis hinted at a negative correlation of TMEM59L expression with CD8 T cells, activated CD4 T cells, and several immunomodulators, including IDO1, TIGIT, PD-L1, CTLA-4, and BTLA in various cancers. Survival analysis indicated that the hypermethylation of TMEM59L gene was associated with longer survival times. A significant correlation was also observed between TMEM59L expression and immunophenoscore, homologous recombination deficiency, loss of heterozygosity, tumor stemness score, and neoantigens in various cancers. Importantly, we also identified numerous potential agents that may target TMEM59L. Conclusion: Our study revealed the prognostic value as well as the genomic and immunological characteristics of TMEM59L in cancers, highlighting the promising potential for TMEM59L as a prognostic cancer biomarker and a therapeutic target.